Factors Associated With Caregivers' Resilience in a Terminal Cancer Care Setting. (April 2018) - Hwang, In Cheol; Kim, Young Sung; Lee, Yong Joo; Choi, Youn Seon; Hwang, Sun Wook; Kim, Hyo Min; Koh, Su-Jin
Background: Resilience implies characteristics such as self-efficacy, adaptability to change, optimism, and the ability to recover from traumatic stress. Studies on resilience in family caregivers (FCs) of patients with terminal cancer are rare. This study aims to examine the factors associated with FCs' resilience in a terminal cancer care setting. Methods: This is a cross-sectional study of 273 FCs from 7 hospice and palliative care units in Korea. Resilience was categorized as high and low, and factors associated with resilience were grouped or categorized into subscales. A multivariate logistic regression analysis was used to examine relevant factors. Results: High FCs' resilience was significantly associated with FCs' health status, depression, and social support. In a multivariate regression model, FCs' perception of good health (adjusted odds ratio [aOR] = 2.26, 95% confidence interval [CI] = 1.16-4.40), positive social support (aOR = 3.70, 95% CI = 1.07-12.87), and absence of depression (aOR = 3.12, 95% CI = 1.59-6.13) remained significantly associated with high FCs' resilience. Conclusion: Lack of family support is associated with and may be a cause of diminished resilience. And more concern should be paid to FCs to improve FCs' health and emotional status. Education programs might be effective for improving caregivers' resilience. Further research with supportive interventions is indicated.